STUDY OF RAPID HYDROGEN PRODUCTION FROM WATER ELECTROLYSIS AIDED BY SUPERCAPACITOR - Faisal Prawiratama, Muhammad
Hydrogen has emerged as new energy for vehicles because of its high specific energy and zero carbon emissions. On-site rapid hydrogen production could be a solution for hydrogen storage and distribution. Water electrolysis has gained interest recently as hydrogen production process. However, fluctuating high electric current is difficult to do for the realization of rapid hydrogen production. Supercapacitor has the potential to realize that because of its great charge-discharge ability. This research studied the performance of water electrolysis that uses supercapacitor circuit as its power supply. The electrolysis cell consisted of nickel cathode, Pt/Ir anode, and KOH 1 M electrolyte. Commercial 500 farad EDLC supercapacitors are used in this research with 2,5 V operating voltage. This research varied circuit configurations and numbers of supercapacitor, then the optimum configuration and condition of supercapacitor circuit are determined. Performance of water electrolysis using supercapacitor circuit was also compared to constant voltage water electrolysis. Adding the number of supercapacitors in series correlates positively toward hydrogen production and negatively toward energy efficiency, while parallel configuration showed the opposite correlations. Based on water electrolysis cell used in this research, supercapacitors in series are recommended for rapid hydrogen production with optimum condition was found at 6,05 V of initial voltage. Ten-minutes water electrolysis at those conditions produced 18.5 mL of hydrogen with 29% of energy efficiency. In comparison to constant voltage operation, supercapacitor as power supply of water electrolysis is superior in energy efficiency, but inferior in hydrogen production.